2018
DOI: 10.1007/978-3-319-72041-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of DNA Damage Induced by Cerium Dioxide Nanoparticles: From Models to Molecular Mechanism Activated

Abstract: This chapter will present an original effort to summarize the relevant data about the cyto-genotoxicity induced by cerium dioxide nanoparticles (nanoceria) in physiologically (in vivo and in vitro) relevant models. In this way, this chapter should be extremely useful to everyone who wants to plan their research and publishing their results. Massive application of nanoceria at different fields is increasing year after year, and it is urgent to address and discuss their use and its safety-related issues. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Although some authors have reported the genotoxic effects of CeO 2 NPs, there is no general agreement about this point [35]. It has been proposed that the apparent discordant reported data are the result of both the pro-oxidant and anti-oxidant role of CeO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Although some authors have reported the genotoxic effects of CeO 2 NPs, there is no general agreement about this point [35]. It has been proposed that the apparent discordant reported data are the result of both the pro-oxidant and anti-oxidant role of CeO 2 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative DNA damage may cause the potential genotoxicity of the engineered Cerium nanoparticles, Nanoceria (cerium dioxide nanoparticles). Additionally, a change in ROS generation under changing pH conditions might determine the pro-or antioxidative activities of nanoceria [153]. For example, catalase and SOD mimetic activity reduce oxidative stress depending on their size at a neutral pH, whereas oxidase and peroxidase, activated at an acidic pH, may cause toxic effects and limit their usability [154,155].…”
Section: Acellular Dermal Matricesmentioning
confidence: 99%